2020
DOI: 10.32521/2074-8132.2020.4.111-122
|View full text |Cite
|
Sign up to set email alerts
|

Demographic portrait of Koryaks from Northern Kamchatka

Abstract: Ìàòåðèàëû è ìåòîäû. Ïðîâåäåí àíàëèç äåìîãðàôè÷åñêîé ñòðóêòóðû ïîïóëÿöèè êîðÿêîâ íà ñòûêå àðåàëîâ êîðåííûõ ìàëî÷èñëåííûõ íàðîäîâ -êîðÿêîâ, ÷óê÷åé è ýâåíîâ. Äåìîãðàôè÷åñêèå ïîêàçàòåëè êîðÿêîâ (ïîë, âîçðàñò, ñîñòàâ ñåìüè, òèï áðàêîâ) äëÿ òðåõ ñåë Îëþòîðñêîãî ðàéîíà Êàì÷àòñêîãî êðàÿ ðàññ÷èòàíû íà îñíîâå êíèã ïîõîçÿéñòâåííîãî ó÷åòà íàñåëåíèÿ (íà 2018 ã.). Ñðåäè 2614 aeèòåëåé òðåõ ñåë ïðåîáëàäàþò ïðåäñòàâèòåëè êîðåííûõ íàðîäîâ Äàëüíåãî Âîñòîêà: 27% ÷óê÷è, 21% êîðÿêè, 10% ýâåíû. Ïðèøëîå íàñåëåíèå ïðåäñòàâëåíî ïðåèìó… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…Meanwhile, the results of the study of maternally inherited mtDNA variability in the Koryaks and Evens of the Magadan region showed that they have a very low frequency of European mtDNA variants (up to 4 % in the Evens) (Derenko et al, 2023). The obtained results, thus, testify to a long history of admixture between the indigenous and immigrant populations in the territory of the Magadan region, as well as to the fact that immigrant men were predominantly involved in interethnic marriages and most of the children of such marriages were likely to be registered as indigenous, which is also typical of other areas of Northeastern Siberia according to demographic data (Khakhov skaya, 2003;Balanovska et al, 2020b).…”
supporting
confidence: 65%
“…Meanwhile, the results of the study of maternally inherited mtDNA variability in the Koryaks and Evens of the Magadan region showed that they have a very low frequency of European mtDNA variants (up to 4 % in the Evens) (Derenko et al, 2023). The obtained results, thus, testify to a long history of admixture between the indigenous and immigrant populations in the territory of the Magadan region, as well as to the fact that immigrant men were predominantly involved in interethnic marriages and most of the children of such marriages were likely to be registered as indigenous, which is also typical of other areas of Northeastern Siberia according to demographic data (Khakhov skaya, 2003;Balanovska et al, 2020b).…”
supporting
confidence: 65%